"How can the creative arts possibly be taught online?" Perspectives and experiences of online educators in Australian higher education. Issue 3 (27th May 2021) - Burke, Katie
ABSTRACT: Many universities in Australia and internationally now offer education degrees entirely online, without any requirement for face-to-face learning on university campuses. The transition to online learning has occurred rapidly, and has had particularly strong uptake in Initial Teacher Education. This paper examines the perspectives and experiences of eight academics in Australian higher education who teach creative arts courses to pre-service teachers via online modes of delivery. Research indicates that insufficient opportunities have existed for some time in adequately providing opportunities to pre-service teachers to develop the arts teaching and learning skills, and these concerns are potentially compounded in online contexts which do not readily permit the interpersonal, kinaesthetic and collaborative engagement with arts-specific materials and processes that are usually central to creative arts learning. Using in-depth interviews and thematic analysis, the researcher sought to understand the individual perspectives and experiences of arts academics who now deliver creative arts learning in teacher education online. The research reveals that arts learning must be significantly re-imagined for the online learner, that the potential to do this can be realised, but that additional support will be required to ensure this is a consistent reality.